Seven new species of Bibloplectus Reitter (Coleoptera: Staphylinidae: Pselaphinae) from Eastern United States with notes on distributions of previously described species - Owens, Brittany E.; Carlton, Christopher E. (Zootaxa, 2017)
Seven new species in the genus Bibloplectus Reitter, 1881 are described: Bibloplectus ellisi Owens and Carlton, new species; Bibloplectus levis Owens and Carlton, new species; Bibloplectus parki Owens and Carlton, new species; Bibloplectus quadratum Owens and Carlton, new species; Bibloplectus suteri Owens and Carlton, new species; Bibloplectus steevesi Owens and Carlton, new species; and Bibloplectus tishechkini Owens and Carlton, new species. New species are integrated into the previously published key, supported by illustrations of diagnostic characters, and a revised key and checklist to eastern North American species is presented. All new species described in this study were obtained from, and are deposited in, collections of the Field Museum of Natural History (FMNH). Additionally, label data for 1122 Bibloplectus specimens from the FMNH and from 111 specimens from the Louisiana State Arthropod Museum (LSAM) were combined to provide updated distributional information on existing species and note significant range extensions.